Material requirements planning with a novel lot sizing method and a new algorithm for production scheduling - Seyed Mahdi Javadi; Seyed Jafar Sadjadi; Ebrahim Teimoury; Ahmad Makui (Scientific Reports)
Abstract Material Requirements Planning is an intelligent information system and a decision maker that determines the type of raw materials, the quantity of them, and their supplying time in order to realize production schedule of products and work-in-process items in a manufacturing system. In each manufacturing system, if we split production costs into material, labor, and overhead costs, we will observe that over 60% of total production costs are related to material. Therefore, it is necessary to consider an appropriate inventory control system to manage the costs of inventory system to provide right inventory, with right quantity, at the right time, at the right price, and with appropriate quality. Lot sizing methods in previous researches do not provide feasible and operational solutions, or have parameters such as holding costs and set up costs that are not identified in financial accounts. To solve this research gap, in this paper, we presented a new lot sizing method considering two important parameters including batch size of the items and the minimum order quantity that a supplier provides for the items. Simultaneously, we designed a new production scheduling algorithm in Master Production Schedule component for a manufacturing system with k production lines and m products with n Bill of Materials for each product. At the end, we programmed our new mentioned contributions and developed Material Requirements Planning module of a Supply Chain Management system.